Universo cristão de corações abrasados e suas afinidades sociorreligiosas - Piedade, Eduardo (2020)
The dissertation listed occurrences of aesthetic, symbolic, liturgical and ritualistic scope from the Brazilian Methodist Pentecostal universe with constituents of exponential organizations, in order to confirm the hypothesis of an elective affinity with socio-cultural reinforcement between both. The project used empirical research methodology and historical survey of the origin of the Methodist movement, considering the fundamental theoretical productions of the researchers Frank Usarski for the constituents of the science of religion, Peter Ferdinand Drucker and Idalberto Chiavenato for science of administration, Ismail Salim for the culture of exponential organizations and Max Weber to relate religiosity and sociology about legitimate obedience and elective affinities involved in the hypothesis. We also have historical reports, definitions related to Protestantism and World and Brazilian Pentecostalism by Isael Araújo, Jean Pierre Bastian, Joanildo A. Machado Burity, Émile G. Léonard, Antonio G. Mendonça and Richard Shaull; statutes, diaries and publications of John Wesley and Episcopal College of the Methodist Church. The studies confirmed the hypothesis of an elective affinity with socio-cultural reinforcement between the occurrences identified in the Brazilian Methodist Pentecostal universe and the structuring constituents of the culture of exponential organizations, among others by the adhesion of 9 of the 11 elements of their systematizations, representing 81.81% potential socio-cultural reinforcement